O uso do vocabulário controlado para informação LGBTQIAP+ no portal brasileiro de publicações e dados científicos em acesso aberto (OASISBR) - Silva, Janael Sousa da (Brasil, 2023)
This research aimed to analyze the presence and treatment of terms related to the LGBTQIAP+ community in OASISBR, an important source of academic information. The LGBTQIAP+ community has been the object of study and discussion in several areas of knowledge, and understanding the terminology used in this context is essential for promoting inclusion and equality. The study also considered the importance of controlled vocabulary and documentary language in this analysis. The controlled vocabulary consists of a set of standardized and structured terms, used to index and retrieve information accurately and consistently. Documentary language, in turn, refers to the set of techniques and processes used to describe and represent information contained in documents. This language is essential for the efficient organization and retrieval of documents, providing users with the ability to find relevant information quickly and accurately. In the present study, the proper use of documentary language contributed to the identification and analysis of the most relevant terms within the universe of the LGBTQIAP+ community. The analysis was based on a list of terms selected from the LGBT Communication Manual and the Communication and LGBT language, aiming to understand the relevance and distribution of these terms in the different types of documents found. With this analysis, we tried to understand the reasons and motives that led these terms to be the most relevant in their respective categories. Factors such as frequency of use, topicality and relevance of the term within the LGBTQIAP+ context were considered. In conclusion, the research carried out at OASISBR allowed a comprehensive analysis of terminologies related to the LGBTQIAP+ community, taking into account the importance of controlled vocabulary and documentary language. The results obtained contribute to a better understanding of the academic discourse on the LGBTQIAP+ community, providing relevant insights for future research and promoting greater accuracy and consistency in indexing and retrieving information.